Influence of Gender and Job Status on Bank Workers’ Level of Work-Family Conflict Depression Experienced in Enugu State, Nigeria - D. I., Ugwu; C. E., Ezedum (Journal of Home Economics Research, 2024)
The study determined the levels of work-family conflict depression experienced by bank workers based on gender and job status in Enugu state, Nigeria. Two null hypotheses were tested at 0.05 level of significance. The population for the study consisted of 2021 bank workers. Two sets of questionnaire were used for data collection. Mean scores and t-test were used for data analysis. Results revealed that both the male and female and senior and junior bank workers experienced moderate levels of work family conflict depression. There is no significant differences between mean levels of male and female and senior and junior bank workers’ work-family conflict depression experience. It was recommended, among others, that proper orientation should be given to new workers on their susceptibility to work family stress, the antecedents and consequences of work-family conflict.